(untitled) (Journal of Engineering, 2024)
To render the environment amenable, is the great challenge to the man in general & to the architect in particular, since the beginning cf the creation up to this date, with a view to reaching physical, physiological, & psychological environment, as to ensure certain immunity from the problems of cross internal & external environmental pollution in "Clean Buildings ", expressing his successful attempts at arriving at the results of the environment influences in the of the man’s needs & desires and construing his relationship with the given environment to an actual existence features & components , on the ground that the planning of the building , designing its spaces & landmarks ,distributing its openings , & nature of the building materials used with the engineering services & technologies utilized in each work , resembles the function of the lenses which gathers the various environmental input & release the output & impacts which are " the Clean Buildings " The specific problem of the research is therefor, the absence of clear & specialized knowledge, of the basic relationship between architecture & environmental pollution influences through the technical, technological & environmental constraints with the object of creating clean buildings of high performances.